Navigating an uncertain interregnum - Boland, Neil (Frontiers in Education, 2024)
This article seeks to identify trends in Steiner Waldorf education through the lens of Clarence Beeby’s work on educational myths. Beeby calls myths a form of communication between contemporaries or between generations, ways of conceptualizing education that can be understood quickly yet are flexible enough to accommodate a range of interpretations. A myth holds for a period and then transitions into a new myth that best suits changed times and changed circumstances. I reflect on what the myths of Waldorf education might be and take up Gramsci’s well-known quotation on change, “The crisis consists precisely of the fact that the old is dying and the new cannot be born; in this interregnum a great variety of morbid symptoms appear,” In writing this, Gramsci extended the interregnum beyond its usual papal connotation to include the socio-cultural condition as well. I use the notion to consider if Waldorf education is currently in an interregnum period and is displaying both “morbid symptoms” and promising signs of fresh development. In addition, I contemplate if these promising signs point toward a new myth that will allow Waldorf education to step beyond its century-old, colonial heritage.